Evaluación de estrategias integradas para el control de mosca blanca (Bemisia tabaci), en el cultivo de pimiento (Capsicum annuum L.) en el cantón Catamayo, provincia de Loja – Ecuador. - Peñarrieta Zamora, Ginger Lisbeth (2024)
The objective of this research was to evaluate integrated strategies for the control of whitefly (Bemisia tabaci) in the bell pepper crop under field conditions in Loja province, Catamayo canton, of El Porvenir neighborhood. The trial was conducted using a completely randomized block design (CRAB) with four treatments and four replications; the application costs of the treatments and the profitability of the production were also determined. The variables evaluated were incidence rate, severity and yield. The effect of the treatments on the dependent variables was performed by means of a simple analysis of variance (ANOVA) with Tukey's multiple comparison tests at 0.05%. Within the diagnostic evaluation, the results of the bioassay showed considerable significant differences between treatments, of which the most effective was the chemical treatment with a reduction in incidence percentage of 16.94 % and severity of 6.24 %, followed by the biological control that reduced incidence to 23.68 % and severity to 7.96 % and the ethological control with incidence values of 37.64 % and severity of 10.08 %. The analysis of the costs of the treatments in relation to the levels of effectiveness and the yields achieved showed that all had higher yields than the absolute control treatment and B/C ratios higher than 1.0, which had a positive impact, highlighting the chemical control with a B/C ratio of 1.50 and a profitability of 4,932.44 USD/ha.